Constructing the taxonomy of educational objectives in light of the role of the messengers of god in Islam - Jamil, Khairil Husaini; Jamil, Asyraf Isyraqi (2019)
This paper aims at proposing a teaching and learning taxonomy that can be derived from the Qurʾanic verses and the prophetic ḥadīths that address the roles and objectives of the messengers of God as observed in Islam. Since messengers of God were not only perceived as the bearers of the commandments but also as educators of their nations, the verses and the dicta pertaining to this role may have shed some light on crafting the bases for the taxonomy of learning. Some of these scriptural references include the verses “Our Lord, make a messenger of their own rise up from among them, to recite (tilāwah) Your revelations to them, teach them the Scripture (al-Kitāb) and wisdom (al-Ḥikmah), and purify (tazkiyah) them: You are the Mighty, the Wise” (Qurʾān 2:129), “Just as We have sent among you a Messenger of your own to recite Our revelations to you, purify you and teach you the Scripture, wisdom, and [other] things you did not know.” (Qurʾān 2:151), “God has been truly gracious to the believers in sending them a Messenger from among their own, to recite His revelations to them, to make them grow in purity, and to teach them the Scripture and wisdom- before that they were clearly astray” (Qurʾān 3:164), and “It is He who raised a messenger, among the people who had no Scripture, to recite His revelations to them, to make them grow spiritually and teach them the Scripture and wisdom –before that they were clearly astray–“ (Qurʾān 62:2). The conclusive analysis of comparison between one hundred exegetical works (tafāsīr) on the abovementioned verses will be presented. This paper ventures into this subject without embedding any previous models such as the Bloom’s taxonomy or the Anderson’s revision. However, a brief comparison may be provided towards the end of the article. The ultimate aim is to understand how observant Muslims can follow in the footsteps of the messengers of God with regards to educational activities and endeavours. It is also hoped that this paper will make a significant contribution to the literature and progress of Islamic education.